2021
DOI: 10.1039/d1ra01358k
|View full text |Cite
|
Sign up to set email alerts
|

Effects of morphology and pore size of mesoporous silicas on the efficiency of an immobilized enzyme

Abstract: Mesoporous silica films were used as supports with high loading capacity and enzyme activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 42 publications
2
14
0
Order By: Relevance
“…It was suggested that more protein could be adsorbed in the larger pores, although desorption is favored, and the dense arrangement hampers conformational flexibility with concomitant loss of activity [124]. This overall pattern had also been previously reported by Takimoto and co-workers [125] while immobilizing cellulase in mesoporous materials with pore sizes ranging from 5.4 to 11 nm. Kuo and co-workers also highlighted the relevance of pore morphology in enzyme performance.…”
Section: Geometry and Pore Size And Morphology Of The Carriersupporting
confidence: 76%
“…It was suggested that more protein could be adsorbed in the larger pores, although desorption is favored, and the dense arrangement hampers conformational flexibility with concomitant loss of activity [124]. This overall pattern had also been previously reported by Takimoto and co-workers [125] while immobilizing cellulase in mesoporous materials with pore sizes ranging from 5.4 to 11 nm. Kuo and co-workers also highlighted the relevance of pore morphology in enzyme performance.…”
Section: Geometry and Pore Size And Morphology Of The Carriersupporting
confidence: 76%
“…SBA-15 is a hexagonal mesoporous silica ( Figure 3 a) with a high specific surface area and pore size that is often used for enzyme immobilization. Kuo et al [ 79 ] immobilized Streptomyces griseus HUT 6037 in three different mesoporous matrices: mesoporous silica film, mesocellular foam, and rod-like SBA-15. Their study demonstrated that all three immobilized materials exhibited more than 90% enzyme loading at optimal pH with efficient performance and reusability, indicating that the mesoporous materials improved the chemistry and stability of the enzyme.…”
Section: Overview Of Immobilization Technologymentioning
confidence: 99%
“…Recently, Kuo et al investigated the effects of morphology and pore size of silica nanoparticles on the efficiency of enzyme immobilization using Streptomyces griseus HUT 6037 enzyme as a model enzyme and three different silica nanoparticles as supports. [18] It was reported that the loading capacity of the immobilized enzyme mainly depended on the surface charge of the particle, and the enzyme activity was related to the support type. Film-type mesoporous silica with short nanochannel length could maximize the accessibility of the immobilized enzyme to the environment, therefore achieving the highest activity.…”
Section: Enhanced Enzyme Activitymentioning
confidence: 99%